Regulation of metabolic health and adipose tissue function by group 2 innate lymphoid cells - Cautivo, Kelly M. (Eur J Immunol, 2016)
Adipose tissue (AT) is home to an abundance of immune cells. With chronic obesity, inflammatory immune cells accumulate and promote insulin resistance and the progression to type 2 diabetes mellitus (T2DM). In contrast, recent studies have highlighted the regulation and function of immune cells in lean, healthy adipose tissue, including those associated with type 2 or “allergic” immunity. Although traditionally activated by infection with multicellular helminthes, AT type 2 immunity is active independently of infection, and promotes tissue homeostasis, adipose tissue “browning”, and systemic insulin sensitivity, protecting against obesity-induced metabolic dysfunction and T2DM. In particular, group 2 innate lymphoid cells (ILC2s) are integral regulators of AT type 2 immunity, producing the cytokines IL-5 and IL-13, promoting eosinophils and alternatively activated macrophages, and cooperating with and promoting AT regulatory T (Treg) cells. In this review, we focus on the recent developments in our understanding of ILC2 cells and type 2 immunity in adipose tissue metabolism and homeostasis.